Requirements for systemic sclerosis expert centres in the Netherlands: A Delphi consensus study. Issue 1 (February 2021) - Spierings, Julia; Schriemer, Rita; Dittmar, Sonja; de Pundert, Lian; de Vries-Bouwstra, Jeska; van den Ende, Els; Vonk, Madelon
Introduction: Systemic sclerosis is a rare and complex disease. Optimal management of patients requires knowledge and experience and, importantly, intensive collaboration between hospitals and multidisciplinary teams. Definition and recognition of expert centres in systemic sclerosis is currently lacking, which complicates collaboration between centres and leaves patients poorly informed. The aim of this study was to develop a set of requirements for two types of systemic sclerosis centres in order to establish a nationwide structure for an optimal and transparent organization of care. Methods: A three-round Delphi study was conducted among a panel of rheumatologists working at university or regional hospitals across the Netherlands. Prior to the final consensus round, a session with a patient panel (N = 22) was held. The results of this meeting were described in the last round for rheumatologists. Criteria were divided into five categories: (1) medical care, (2) case load, (3) collaboration, (4) research, (5) training of staff, and (6) other. In the first round, criteria derived from literature were proposed and participants could add criteria that were missing. For every item, participants could indicate if they thought the item should be included for two types of systemic sclerosis centres: (1) systemic sclerosis expert centre or (2) systemic sclerosis treatment centres. Consensus was reached when more than 85% of the panel agreed. Results: In total, 47 rheumatologists participated in Delphi round 1, 35 in round 2 and 43 in round 3. Additional suggestions were added by the patient panel (n = 22). Consensus was reached for the requirements of systemic sclerosis expert centres (45 items) and systemic sclerosis treatment centres (29 items) including minimal caseloads of annual suspected systemic sclerosis cases and total patients in care. Conclusion: Requirements of centres for systemic sclerosis care in the Netherlands were established in this study. Feasibility of certification should be evaluated next. Our proposed list can serve as a model for other countries.